Tinjauan Penyebab Terjadinya Misfile Dokumen Rekam Medis Rawat Jalan Di RSUD Kabupaten Jombang Tahun 2020 - Krisnita Dwi Jayanti; Ratna Frenty Nurkhalim; Ninda Mulya Ike Ardila; Budi Pranoto; Indra Setyawan; Indah Susilowati (Akademi Perekam dan Informasi Kesehatan Imelda, 2022)
Medical record outpatient and emergency must be accompanied and completed after service to patiens the same day. This study aims to find out the factors that cause misfile from the management aspects of man, method, machine, and material in Jombang District Hospital. This research is descriptive qualitative with a case study approach. The sample in this study were 11 officers. Data collection techniques used are questionnaires and observation sheets. The results showed that in the man element, it was found that the problem of the absence of medical record officers with a background in medical record education where it is also a trigger for misfile in the filing room, the absence of training for medical record officers due to the lack of programs related to medical record training in Jombang District Hospital, and officers have never been rewarded in any form such as praise or incentives and penalties to be motivated to work better. In the method element found the problem of the absence of the implementation of medical record documents investigation activities every day periodically by officers to prevent the occurrence of misfile. On the machine element found problems of not using tracer and outguide. In the material element found the problem is that the color code in Jombang District Hospital is not applied in its entirety because of the lack of importance of color coding officers to prevent misfiles. It can be suggested that leaders should provide rewards and punishments, participate in training, make policies related to DRM investigation activities, tracer implementation, and color coding on DRM covers.